ANALISIS PERBANDINGAN INDEKS HARGA SAHAM SEBELUM DAN SESUDAH PENETAPAN FATWA MUI TENTANG PEMBOIKOTAN PRODUK-PRODUK YANG TERAFILIASI DENGAN ISRAEL: - Purnomo, Endri (Nusantara Hasana Journal, 2024)
This study aims to analyze the differences in stock prices of companies affiliated with Israel before and after the issuance of the MUI fatwa recommending a boycott of Israeli products. Using a quantitative approach, this study evaluates the stock performance of PT Unilever Indonesia Tbk (UNVR), PT MAP Boga Perkasa Tbk (MAPB), and PT Erajaya Swasembada Tbk (ERAA). The findings of the study show a significant impact of the MUI fatwa on the stock price fluctuations of the three companies, highlighting the economic implications of socio-political action. The results of this study are useful for policymakers and investors in anticipating market responses to similar situations.